2015
DOI: 10.7314/apjcp.2015.16.12.4927
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Risk Factors for Nasopharyngeal Carcinoma in a High-risk Area of India, the Northeastern Region

Abstract: generally been classified as high-or low-incidence areas, the racial/ethnic distribution of NPC within regions is far from uniform (Chang and Adami, 2006). In the southeastern Chinese province of Guangdong, where the overall NPC incidence rate is >20 per 100,000 personyears among males, rates in Cantonese speakers are double those in other dialect groups such as the Hakka, Hokkien, and Chiu Chau (Parkin et al., 2002;Chang and Adami, 2006). Likewise, in the Malaysian state of Selangor, rates in Chinese residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 49 publications
(55 reference statements)
3
14
0
Order By: Relevance
“…In this study, Minangkabau ethnicity in both NPC and controls group found only heterozygote mutants (c1c2), and not related to the incidence of NPC. The same was reported by Lourembam et al who conducted a study in India in areas with a high incidence of NPC also found only heterozygote polymorphisms and also did not get a significant relationship with the incidence of NPC [3]. Hildesheim et al, [2].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In this study, Minangkabau ethnicity in both NPC and controls group found only heterozygote mutants (c1c2), and not related to the incidence of NPC. The same was reported by Lourembam et al who conducted a study in India in areas with a high incidence of NPC also found only heterozygote polymorphisms and also did not get a significant relationship with the incidence of NPC [3]. Hildesheim et al, [2].…”
Section: Discussionsupporting
confidence: 58%
“…Various environmental factors have been reported related to the incidence of Nasopharyngeal Carcinoma (NPC), including consumption of salted fish containing nitrosamines [2], [3]. Study on environmental factors as carcinogens has varied reports, but in endemic areas, nitrosamines from salted fish are a factor that is often associated with the incidence of NPC [3]. but clinical study at Dr. RSUP M. Djamil Padang did not get this association [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the univariate analysis, we considered the impact of several covariates such as age, gender, urbanization level, insurance fee level, HT, COPD, HL, DM, CS, asthma, EBV infection-related diseases, occupational types and alcoholism, which are associated with tumor development [ 26 30 ]. In addition, several studies have reported that active smoking and alcohol consumption are associated with increased NPC risk [ 31 , 32 ]. Nevertheless, the major limitations of the NHIRD is attributed to insufficient information on family history and lifestyle activities such as smoking and alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic alteration, virus infection, and exposure to the environmental factors are the major factors of NPC [2]. Although radiotherapy and chemotherapy are very effective for most of NPC, 30-40 % of NPC still progress into the distant metastasis, and the metastasis is the major cause for the NPC-related death [3].…”
Section: Introductionmentioning
confidence: 99%